IFN-γ-mediated control of SARS-CoV-2 infection through nitric oxide - Silva, Bruno J. de Andrade; Krogstad, Paul A.; Teles, Rosane M. B.; Andrade, Priscila R.; Rajfer, Jacob; Ferrini, Monica G.; Yang, Otto O.; Bloom, Barry R.; Modlin, Robert L. (Frontiers in Immunology, 2023)
The COVID-19 pandemic has highlighted the need to identify mechanisms of antiviral host defense against SARS-CoV-2. One such mediator is interferon-y (IFN-y), which, when administered to infected patients, is reported to result in viral clearance and resolution of pulmonary symptoms. IFN-y treatment of a human lung epithelial cell line triggered an antiviral activity against SARS-CoV-2, yet the mechanism for this antiviral response was not identified. Given that IFN-y has been shown to trigger antiviral activity via the generation of nitric oxide (NO), we investigated whether IFN-y induction of antiviral activity against SARS-CoV-2 infection is dependent upon the generation of NO in human pulmonary epithelial cell lines. Treatment of Vero E6 cells with IFN-y resulted in a dose-responsive induction of NO and an inhibitory effect on SARS-CoV-2 replication. This antiviral activity was blocked by pharmacologic inhibition of iNOS. IFN-y also triggered a NO-mediated antiviral activity in SARS-CoV-2 infected human lung epithelial cell lines A549-ACE2 and Calu-3. IL-1B enhanced IFN-y induction of NO, but it had little effect on antiviral activity. Given that IFN-y has been shown to be produced by CD8+ T cells in the early response to SARS-CoV-2, our findings in human lung epithelial cell lines, of an IFN-y-triggered, NO-dependent, links the adaptive immune response to an innate antiviral pathway in host defense against SARS-CoV-2.